PERSEPSI MASYARAKAT TERHADAP TATA CARA PENOBATAN GELAR PANGULU NAN BAROMPEK DI KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - R Kurniawati '; Hambali '; Ahmad Eddison (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study is based on a problem how Pangean Against Public Perception Procedure Crowning Pangulu Nan Barompek degree in Kenegerian Pangean Singingi Regency Kuantan. Perception in this sense refers to the three elements, namely: (1) Selection Process pangulu barompek nan, (2) The series of events, and (3) The Coronation of Indigenous degree. Sample size was 35 respondents. The purpose of this coronation customary title is that these people have traditional leaders so that the custom is not lost. (Azizah, 2000). The problems of this research is How Public Perception Of Coronation Procedures Pangulu Nan Barompek degree in Kenegerian Pangean Singingi Kuantan District. This study aims Knowing Bagaiamanakah Procedures Against Public Perception Crowning Pangulu Nan Barompek degree in Kenegerian Pangean Singingi Regency Kuantan. This research was conducted in the District of Pangean Regency Kuantan Singingi lasted from February to May 2014. Population in this study were all Pangean society Subdistrict totaling 18 957 people. The sampling technique was purposive sampling technique, the sample in this study was 35. Data collection techniques used were in the form of observation, questionnaire techniques, interview techniques, technical documentation, and library research techniques. In analyzing the data using qualitative methods deskripstif simple. Adapaun hypothesis in this research is the perception Societies Procedures Crowning Pangulu Nan Barompek degree in District Pangean Kuantan District Singingi "Not Good". The results of this study indicate that the District Public Pangean Singingi Regency Kuantan with a percentage of 43.8% and included into the category benchmark for "good enough" is the benchmark of 25.01% -50.00%. So the hypothesis: Public Perception Of Degree Crowning Pangulu Procedures in the District of Nan Barompek Pangean Regency Kuantan Singingi "good enough" is acceptable.Keywords: Perception, Coronation Pangulu Nan Barompek, Kenegerian Pangean